Orte und Nicht-Orte in Paul Celans Engführung (1959) - Jan T. Schlosser (Recherches Germaniques)
While Celan research until now was focused on biographical and linguistic references, the purpose of this article is to establish an anthropological frame of reference for the analysis of the poem Engführung, in which Celan thematises a transformed anthropological room. Celan’s literary anticipation of Marc Augé’s theory Places and Non-Places is central. Celan does not accept the postmodern claim that the idea of progress has collapsed. The anticipation of super-modernity takes place in Engführung in the sense that the search of meaning is recognisable as opposed to the dominance of non-places. Celan endeavours to establish places with cultural and historical identity.